License to kill - Farentino, James, 1938-; Murray, Don, 1929-; Fuller, Penny; Perkins, Millie, 1938-; Washington, Denzel, 1954-; Taylor, Jud, 1940-; Platinum Disc Corporation (La Crosse, WI : Platinum Disc Corp., 2004)
Parents of a high school girl killed in an automobile accident file vehicular manslaughter charges against the man who was driving while intoxicated.
Videodisc release of the 1984 television motion picture.
James Farentino, Don Murray, Penny Fuller, Millie Perkins, Denzel Washington.
Rated 13.
DVD.
Keywords: Drunk driving -- Drama; Legal drama